Assessing the role of the San Miguel multi-purpose cooperative in achieving empowerment of the people. - Signar, Karen Grace B. (Tacloban City Karen Grace B. Signar, 2009)
Wherever, people live together as a group, they normally promote and maintain communal life together and a feeling of fellowship is generated. The concept of cooperation and the idea of people empowerment through the conduct of cooperative movement were given much attention in this study. This exploration of empowerment was based from the observation of a multi-purpose cooperative in Hindang, Leyte. The research focused on the perspectives and statements of the members and staff of the cooperative in the context of democratization and development. This study also defined and examined variables affecting the role of San Miguel Multi-Purpose Cooperative in the community. The results of this study explains that while a huge number of members were very much willing and participative in decision makings and goal settings, for some reasons some others were not. It also shows that there are factors that impede the development and those that enhanced empowerment of the members. Moreover, this particular study was done with a four-pronged objective and a reliable conceptual framework that covers interaction of members, equity of benefits, solidarity, and sense of ownership. Indeed, empowerment was seen through these indicators and that cooperatives affects innumerable day-to-day lives as it safeguards members from economic, social and cultural woes.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban.
Keywords: Social Science